2022
DOI: 10.3389/fsurg.2022.859269
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Negative Psychological Stress Response in Elderly Patients With Femoral Neck Fracture by Integrated High-Quality Nursing Model of Medical Care

Abstract: ObjectiveThe objective of this study was to explore the nursing effect and negative psychological stress response of elderly patients with femoral neck fracture by applying the high-quality nursing mode of medical care.MethodsA total of 130 elderly patients with femoral neck fractures hospitalized in our hospital from January 2020 to June 2021 were randomly divided into the control group and observation group, with 65 patients in each group. The control group adopted the conventional nursing mode, while the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The highest score of Frankl is 4. The higher the score, the better the compliance [ 22 ] To study the self-efficacy scale (GSES) scores of the two groups before nursing and after 3 months of nursing. The score of GSES ranges from 10 to 40.…”
Section: Methodsmentioning
confidence: 99%
“…The highest score of Frankl is 4. The higher the score, the better the compliance [ 22 ] To study the self-efficacy scale (GSES) scores of the two groups before nursing and after 3 months of nursing. The score of GSES ranges from 10 to 40.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the two groups of patients had different degrees of incision infection, abdominal pain and distension, adhesive intestinal obstruction, abdominal abscess, vomiting, and other adverse reactions, but they were effectively improved or disappeared after symptomatic treatment. The goal of the integrated medical care mode is to provide patients with holistic medical services that combine nursing, rehabilitation, and treatment provided by medical teams [37,38]; these services can enhance the communication and cooperation between doctors and patients, shorten the postoperative hospitalization time of patients, and improve patient satisfaction [39]. In this study, rapid rehabilitation surgery with integrated medical care combining with routine nursing methods was employed in the perioperative nursing of pediatric laparoscopic surgery for appendicitis, which reduced the physical and psychological traumatic stress of patients, reduced the incidence of complications, and shortened the postoperative rehabilitation process of patients, thus achieving the goal of improving the quality of medical and nursing services and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological stress refers to the adaptive nervous response to the imbalance in objective requirements and coping ability under the action of certain environmental stimuli, including emotional, self-psychological defense, and behavioral responses[ 6 ]. Studies have shown that patients with FNF experience different degrees of negative psychological states and stress reactions[ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%